2017
DOI: 10.1186/s13148-017-0408-5
|View full text |Cite
|
Sign up to set email alerts
|

Newborn genome-wide DNA methylation in association with pregnancy anxiety reveals a potential role for GABBR1

Abstract: BackgroundThere is increasing evidence for the role of prenatal stress in shaping offspring DNA methylation and disease susceptibility. In the current study, we aimed to identify genes and pathways associated with pregnancy anxiety using a genome-wide DNA methylation approach.MethodsWe selected 22 versus 23 newborns from our Prenatal Early Life Stress (PELS) cohort, exposed to the lowest or highest degree of maternal pregnancy anxiety, respectively. Cord blood genome-wide DNA methylation was assayed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 65 publications
2
26
0
2
Order By: Relevance
“…Analysis of DNA extracted from cord blood from neonates demonstrated that gestational age can be reliably predicted between 24 and 44 weeks 10 . These results are consistent with results from induced pluripotent stem cells (iPSCs) that show they are considerably younger than the cells they were derived from 3,11 .…”
Section: Introductionsupporting
confidence: 90%
“…Analysis of DNA extracted from cord blood from neonates demonstrated that gestational age can be reliably predicted between 24 and 44 weeks 10 . These results are consistent with results from induced pluripotent stem cells (iPSCs) that show they are considerably younger than the cells they were derived from 3,11 .…”
Section: Introductionsupporting
confidence: 90%
“…But there was no evidence of sexually dimorphic effects of maternal prenatal cortisol in this study [51]. Similarly, Vangeel et al ( N  = 45) found an interaction such that prenatal anxiety was positively associated with cord blood DNA methylation in the GABA-B receptor subunit 1 gene ( GABBR1 ) in infant boys but not girls [53]. Mina et al found sex-specific associations suggesting that infant girls might be particularly susceptible to the effects of prenatal maternal distress on placental mRNA levels of genes regulating fetal glucocorticoid exposure and placental growth [68].…”
Section: Resultsmentioning
confidence: 64%
“…As there is accumulating evidence for sex differences in DNA methylation changes associated with adverse prenatal exposures [51][52][53][54], we explored differences in the methylation signatures associated with GDM exposure in male versus female infants (Table J in S1 Data). In PLOS MEDICINE…”
Section: Identification Of Dmcpgs In Cord Blood Associated With Matermentioning
confidence: 99%